Does Listening to Music Improve Pain Perception and Anxiety in Patients Undergoing Cystoscopy: A Meta-Analysis - Chen, Guo; Tang, Cai; Liu, Yuebai; Liu, Yuhao; Dai, Yi; Yang, Luo (Frontiers in Surgery, 2021)
Objective: Identify the effect of music on outpatient-based cystoscopy. Methods: We systematically reviewed the effect of using music during all reported outpatient cystoscopy and extract data from randomized trials from inception to December 31, 2020, with no language restrictions. The analysis was completed via STATA version 14.2. Results:A total of 27 studies were initially identified, and six articles containing 639 patients were included in the final analysis. In terms of postprocedural pain perception, a pooled analysis of six articles containing 639 patients showed that music seems to improving discomfort in patients who undergo cystoscopy (WMD: -1.72; 95%CI: -2.37 to -1.07). This improvement remained consistent in patients undergoing flexible cystoscopy (FC) (WMD: -1.18; 95%CI: -1.39 to -0.98) and rigid cystoscopy (RC) (WMD: -2.56; 95%CI: -3.64 to -1.48). The music group also had less postprocedural anxiety than those in no music group during cystoscopes (WMD: -13.33; 95%CI: -21.61 to -5.06), which was in keeping with the result of FC (WMD: -4.82; 95%CI: -6.38 to -3.26) rather than RC (WMD: -26.05; 95%CI: -56.13 to 4.04). Besides, we detected a significantly lower postprocedural heart rate (HR) in the music group than no music group during cystoscopes (WMD: -4.04; 95%CI: -5.38 to -2.71), which is similar to the results of subgroup analysis for FC (WMD: -3.77; 95%CI: -5.84 to -1.70) and RC (WMD: -4.24; 95%CI: -5.98 to -2.50). A pooled analysis of three trials indicated that patients in music group had significantly higher postoperative satisfaction VAS scores than those in no music group during RC. However, there was no significant difference between music group and no music group regarding postprocedural systolic pressures during cystoscopes (WMD: -3.08; 95%CI: -8.64 to 2.49). For male patients undergoing cystoscopy, the music seemed to exert a similar effect on decreased anxiety and pain, and it might serve as a useful adjunct to increase procedural satisfaction. Conclusions: Our findings indicate that listening to music contributes to the improvement of pain perception, HR, and anxiety feeling during cystoscopes, especially for male patients undergoing RC. Music might serve as a simple, inexpensive, and effective adjunct to sedation during cystoscopy.